1991
DOI: 10.1016/0304-3959(91)90126-i
|View full text |Cite
|
Sign up to set email alerts
|

Study of experimental pain measures and nociceptive reflex in chronic pain patients and normal subjects

Abstract: This study evaluates (i) the effect of heterotopic chronic pain on various experimental pain measures, (ii) the relationship between experimental pain measures and chronic pain symptomatology assessment, and (iii) the influence of the various pain aetiologies on experimental pain measures. Fifty-three chronic pain patients were compared to 17 pain-free subjects with the following psychophysical and physiological indices: pain threshold (PTh), pain tolerance (PTol), verbal estimation of intensity and unpleasant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 28 publications
5
47
0
Order By: Relevance
“…Starting from the bottom of the graphic, the scale was labeled one (sensory threshold), 25 (uncomfortable), 50 (painful), 75 (very painful), and 100 (maximum tolerable). Similar rating scales have been used in previous NFR studies (Willer et al, 1979;Chan and Dallaire, 1989;Page and France, 1997;Suchowiecki, 1999, 2001;Anderson et al, 2000), and individual pain ratings have been shown to correlate significantly (r = 0.58-0.95) with NFR thresholds (Chan and Dallaire, 1989;Porchet et al, 1990;Boureau et al, 1991;Dowman, 1991). In general, numerical pain rating scales have been shown to have high levels of reliability and validity in the assessment of pain intensity, and scores obtained from such scales can be treated as ratio data (Jensen and Karoly, 1992).…”
Section: Assessment Of Nfr-aftermentioning
confidence: 85%
“…Starting from the bottom of the graphic, the scale was labeled one (sensory threshold), 25 (uncomfortable), 50 (painful), 75 (very painful), and 100 (maximum tolerable). Similar rating scales have been used in previous NFR studies (Willer et al, 1979;Chan and Dallaire, 1989;Page and France, 1997;Suchowiecki, 1999, 2001;Anderson et al, 2000), and individual pain ratings have been shown to correlate significantly (r = 0.58-0.95) with NFR thresholds (Chan and Dallaire, 1989;Porchet et al, 1990;Boureau et al, 1991;Dowman, 1991). In general, numerical pain rating scales have been shown to have high levels of reliability and validity in the assessment of pain intensity, and scores obtained from such scales can be treated as ratio data (Jensen and Karoly, 1992).…”
Section: Assessment Of Nfr-aftermentioning
confidence: 85%
“…The predominant reason for study exclusion was the lack of pain (or the reporting of) at the time of testing or the absence of a healthy control group. An additional three articles (Boureau et al, 1991;Leroux et al, 1995;Neziri et al, 2012) were found by searching the reference lists of included articles and relevant reviews. This left a total of 36 articles to be included in the review.…”
Section: Discussionmentioning
confidence: 99%
“…Of the included studies, 12 reported reflex threshold (Boureau et al, 1991;Coffin et al, 2004;De Marinis et al, 2007;Sterling et al, 2008;Courtney et al, 2009Courtney et al, , 2010Lim et al, 2012;Neziri et al, 2012;Rhudy et al, 2013;Smith et al, 2013Smith et al, , 2014Curatolo et al, 2015), six reported reflex peak magnitude or AUC or both Avramidis et al, 1998;De Marinis et al, 2007;Peddireddy et al, 2009;Rhudy et al, 2013;Kofler and Halder, 2014), six reported reflex latency (Avramidis et al, 1998;Katsarava et al, 2004;De Marinis et al, 2007;Courtney et al, 2009;Peddireddy et al, 2009;Kofler and Halder, 2014), and two reported reflex duration (Courtney et al, 2009;Peddireddy et al, 2009). Pain populations included 'chronic pain', migraine, migraine without aura, tension type headache, chronic tension type headache, fibromyalgia, rheumatoid arthritis, chronic upper back pain, chronic low back pain, knee osteoarthritis, chronic whiplash associated disorder, irritable bowel syndrome, chronic lateral epicondylalgia ('tennis elbow'), and a combination of idiopathic pain, myofascial pain, and headache (see Table 1 for study details).…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the RIII reXex is considered as a physiological measure of the pain related response (Dowman 1991). In contrast, several studies have shown a disparity between the RIII reXex threshold and Pain threshold (Bromm and Treede 1980;Nord and Durkovic 1988;France et al 2005;Willer et al 1984;Terkelsen et al 2001;Boureau et al 1991;Defrin et al 2007).…”
Section: Introductionmentioning
confidence: 94%